Poikilitic hornblende pyroxenite in the southern end of the Abukuma Mountains, Northeast Japan, as result of adakitic magmatism - Wakazono, Akira; Fukuyama, Mayuko; Itano, Keita; Harigane, Yumiko; Tamura, Akihiro; Morishita, Tomoaki (Frontiers in Geochemistry, 2025)
Amphibole plays a pivotal role in mediating the flux of volatiles and partial melting that ultimately contribute to arc magmatism. The influence of amphibole from the lower crust to the upper mantle remains unclear due to limited opportunities for observation. Amphibole-rich ultramafic rock characterized by large poikilitic hornblende grains with olivine and pyroxenes occurs in the Nishidohira metamorphic rocks in the southern Abukuma Mountains of Northeast Japan (we call poikilitic hornblende pyroxenite hereafter). Amphibole exhibit zoning in color and chemical composition: the dark core has higher TiO2 and Al2O3 contents than the light green rims. Dark-colored high-TiO2 pargasitic amphibole formed early from magmatic melts. Melt compositions calculated from the dark-colored amphibole core based on melt-mineral partitioning indicate that the poikilitic hornblende pyroxenite resulted from adakitic magmatic activity. Reactions between pre-existing ultramafic rock and adakitic melt are likely to form poikilitic hornblende pyroxenite when the melt/rock ratio is low, and hornblende gabbro when the ratio is high. The U-Pb zircon age of approximately 120 Ma for poikilitic hornblende pyroxenite and associated hornblende gabbro is interpreted as a magmatic age. In the Early Cretaceous tectonic framework of Northeast Japan, adakitic magmatism is attributed to the westward subduction of the Izanagi (or Kula) plate beneath the eastern margin of the Eurasian Plate.